Crystals of 4'-substituted nucleosides, their preparation, composition and use
Type III crystals of compound (3) address the challenges of drug resistance and daily administration in HIV treatments by providing a stable, mass-producible form for long-acting AIDS drugs.
Patent Information
- Application Number
- JP2024541205
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-17
- Filing Date
- 2023-01-17
- Publication Date
- 2024-12-23
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Current HIV treatments, despite their ability to suppress the virus, face issues with drug resistance and require daily administration, necessitating the development of long-acting AIDS drugs with new mechanisms of action.
The development of type III crystals of compound (3), which are stable and suitable for pharmaceutical production, offering a crystalline form that can be used in anti-HIV treatments.
Type III crystals of compound (3) exhibit excellent physical properties, facilitating mass production and quality control, making them suitable for long-acting AIDS drugs.
Smart Images

Figure 2024546398000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of medicinal chemistry, and more particularly to crystals of 4'-substituted nucleosides, their preparation methods, compositions and uses. [Background technology]
[0002] HIV infection causes AIDS attacks, and since the first AIDS patient was found in the United States in 1981, there are approximately 39 million AIDS patients in the world. AIDS has already become a serious threat to human health. The replication of the AIDS virus (HIV) is completed through the processes of adsorption, invasion and uncoating, reverse transcription, viral RNA integration and protein synthesis, assembly, release and maturation. Each step of the process can be targeted by HIV inhibitors. After more than 30 years of research, 40 AIDS drugs, including combination drugs, have been approved for clinical use by the US FDA. According to the mechanism of action of these drugs, they are mainly divided into several major categories, such as nucleoside and non-nucleoside reverse transcriptase inhibitors, protease inhibitors, entry inhibitors, and integrase inhibitors. Although these drugs can effectively suppress the replication of HIV, none of them can cure AIDS, and after a certain period of treatment with these drugs, the virus is beginning to develop drug resistance, and the current drug treatment becomes ineffective. Therefore, combining HIV inhibitors with different mechanisms of action to treat AIDS has become a standard treatment strategy. However, even when combined treatment is used to treat AIDS, new drug resistance is still emerging. Therefore, it is still necessary to continue to find AIDS drugs with new mechanisms of action. Currently, all AIDS drugs need to be taken at least once a day, and taking them for a long period of time is a burden on patients, so the development of long-acting AIDS drugs is very necessary.
[0003] 2'-deoxynucleosides are the main HIV inhibitors used in clinical trials, and they exert their pharmaceutical effects by inhibiting reverse transcriptase. Currently, all nucleoside HIV inhibitors in clinical use are 3'-deoxynucleosides. Because they do not have a 3'-OH, after the drug is incorporated into HIV DNA, it stops the elongation of HIV DNA, thereby becoming an HIV DNA synthesis stopper, thereby achieving the effect of inhibiting HIV replication. In recent years, nucleosides with a 3'-OH, such as compound (I) (CAStoddart et al Antimicrob.Agents Chemother.2015,59,4190) and compound (II) (Q.Wang et al Eur.J.Med.Chem.2011,46,4178), have been reported to have significant HIV inhibitory activity. Their structural features are that both have large substituents at the 4'-site, such as an ethynyl group in compound (I) and an azide group in compound (2). By introducing these bulky substituents, these nucleoside phosphates, after being bound to and inserted into viral DNA, slow down or stop the elongation of viral DNA due to their steric effect, thus achieving the purpose of inhibiting HIV replication.
[0004] The introduction of 2-fluoro adenine nucleotides enhances the HIV inhibitory activity of 4'-ethynyl-2'-deoxyadenosine (EC 50 =11 nM) was improved by 2200-fold (EC 50 =0.05nM) (E. Michailidis et al J. Biol. Chem. 2009, 284, 35681).
[0005] A US patent (J. Chang US8835615, 2014) discloses the chemical structure of compound (3) (2R,3R,4S,5R)-5-(6-amino-2-fluoro-9H-purin-9-yl)-2-ethynyl-4-fluoro-2-(hydroxymethyl)tetrahydrofuran-3-ol, and a subsequent Chinese patent (Chang Jun Biao CN109893536 B, 2021) discloses the anti-HIV activity (EC 50=0.9nM) and safety (no obvious cytotoxicity within the measured dose range, CC 50 >8000 nM) was disclosed, along with the crystalline form A of compound (3). DSC and TGA studies revealed that the molecular weight of the compound was 311.24, and crystalline form A lost 9.0% weight at 110°C, indicating that crystalline form A is a solvated crystal containing one molecule of methanol (theoretical methanol content 9.33%) and loses methanol upon heating. [ka] Summary of the Invention
[0006] The present inventors have studied the crystal form of compound (3) intensively and found that compound (3) forms many crystal forms under different conditions. However, most of the crystal forms are unstable. The inventors have unexpectedly found that type III crystal exhibits very good physical properties, such as easy preparation and stable crystal form, which is convenient for mass production and quality control of pharmaceuticals, and is very suitable as a crystal form for pharmaceutical production of compound (3). [ka]
[0007] In view of this, the present invention provides a type III crystal of compound (3), which has characteristic peaks at diffraction angles of 2θ values of 8.83°, 16.08°, 16.53°, 17.67°, 18.19°, 25.52°, 26.20°, and 27.05° in a powder X-ray diffraction pattern using Cu-Kα radiation, with the proviso that changes in the 2θ values within an error range are permitted.
[0008] The diffraction peak data for the type III crystal of compound (3) is as shown in Table 1 below.
[0009] [Table 1]
[0010] The XRPD pattern of the III crystal is shown in FIG. In another aspect, the present invention provides a method for producing type III crystals of compound (3), comprising dissolving compound (3) in 1,4-dioxane / DCM (1 to 5 / 10), adding petroleum ether or a lower alkane (for example, including but not limited to pentane, hexane, octane, nonane, or decane, etc.) to the solution, leaving or stirring for 1 to 24 hours, preferably 3 to 10 hours, more preferably 4 hours, to precipitate crystals, filtering, and subjecting the obtained crystals to vacuum treatment at 25 to 120°C, preferably 40°C to 60°C, for 1 to 24 hours, preferably 3 to 5 hours, to obtain type III crystals.
[0011] The present invention further provides another method for producing type III crystals of compound (3), which comprises stirring compound (3) in ethanol at room temperature for 2 to 72 hours, preferably 20 to 60 hours, and more preferably 48 hours, filtering, and vacuum drying at room temperature to obtain crystals, and heating the obtained crystals to 120 to 150°C, preferably 140 to 145°C, and more preferably 141°C under nitrogen protection to obtain type III crystals of compound (3).
[0012] The present invention further provides another method for producing a III-type crystal of compound (3), which comprises dissolving compound (3) in THF or methyl THF, adding petroleum ether or a lower alkane (e.g., pentane, hexane, octane, nonane, or decane, etc., but not limited thereto) to the obtained solution, adding an appropriate amount of III-type crystal as a seed crystal, obtaining a white suspension, stirring or leaving the obtained suspension at 40°C to 70°C, preferably 50°C, for 1 to 4 hours, preferably 60 to 70 minutes, then gradually lowering the temperature to room temperature, stirring or leaving for an appropriate time, and filtering the obtained suspension under reduced pressure at room temperature, washing with n-heptane, and vacuum drying at 40°C to 80°C, preferably 50°C, to obtain III-type crystal.
[0013] In another aspect, the present invention further provides a pharmaceutical composition comprising the above-mentioned type III crystal of compound (3) and any pharmaceutical auxiliary.
[0014] In another aspect, the present invention further relates to use of the type III crystal of compound (3) or a pharmaceutical composition comprising the type III crystal of compound (3) and any pharmaceutical auxiliary agent for the manufacture of a pharmaceutical preparation or pharmaceutical formulation for anti-HIV or AIDS treatment.
[0015] The present invention further provides a method for anti-HIV or AIDS treatment, comprising administering to a patient an anti-HIV or therapeutically effective amount of the type III crystal of compound (3), or a pharmaceutical composition comprising the type III crystal of compound (3) and any pharmaceutical auxiliary. Effect of the Invention
[0016] The inventors have produced a large amount of crystalline forms of compound (3), most of which are unstable solids. However, the III-form crystal of compound (3) exhibits excellent physical properties, such as easy preparation and stable crystalline form, which is convenient for mass production and quality control of pharmaceuticals, and is suitable as the crystalline form of compound (3) in pharmaceutical production. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is an XRPD diagram of type III crystals. [Diagram 2] FIG. 1 is a TGA / DSC diagram of the III-type crystal. [Diagram 3] FIG. 1 is a comparative variable temperature XRPD diagram of crystal type III. [Figure 4] FIG. 2 is an XRPD diagram of type I crystal. [Diagram 5] FIG. 2 is a TGA / DSC diagram of the I-type crystal. [Figure 6] FIG. 1 is a comparison of XRPD of type I crystals before and after heating to 55° C. [Figure 7] FIG. 1 is an XRPD diagram of type I crystal heated to 100° C. [Figure 8] FIG. 2 is an XRPD diagram of type II crystals. [Figure 9] FIG. 1 is an XRPD diagram of IV crystals. [Figure 10] FIG. 2 is an XRPD diagram of type V crystals. [Figure 11] FIG. 1 is an XRPD diagram of VI type crystal. [Figure 12] FIG. 1 is an XRPD diagram of the VII type crystal. [Figure 13] FIG. 1 is an XRPD diagram of the VIII type crystal. [Figure 14] FIG. 9 is an XRPD diagram of crystal type IX. [Figure 15] FIG. 2 is an XRPD diagram of X-type crystal. [Figure 16] FIG. 1 is an XRPD diagram of XI type crystal. [Figure 17] FIG. 1 is an XRPD diagram of the XII crystal. [Figure 18] FIG. 1 is an XRPD diagram of the XIII type crystal. [Figure 19] FIG. 1 is a comparison of XRPD of type XIII crystals before and after film coating and drying. [Figure 20] FIG. 1 is an XRPD diagram of crystal type XIV. [Figure 21] FIG. 2 is an XRPD diagram of the XV type crystal. [Figure 22] FIG. 2 is an XRPD diagram of the XVI type crystal. [Diagram 23] FIG. 2 is a DSC-TGA diagram of the XVI type crystal. [Figure 24] A three-dimensional view of a single crystal X-ray diffraction molecule of Form XVI. [Diagram 25] FIG. 2 is an XRPD diagram of the XVII crystal. [Figure 26] FIG. 2 is a DSC-TGA diagram of the XVII crystal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be further described below with reference to specific experiments. It should be understood that these experiments are merely illustrative of the present invention and do not limit the technical scope of the present invention. In the following experiments, for the experimental methods for which no specific conditions are specified, general conditions are usually followed or the manufacturer's recommended conditions are followed. Unless otherwise defined, all technical and scientific terms used in the specification have the same meanings as those familiar to those skilled in the art. Any methods and materials similar or equivalent to the described contents can be applied to the method of the present invention. The preferred implementation methods and materials described in the specification are for illustrative purposes only.
[0019] The starting materials in the experiments of the present invention are either known and commercially available or are synthesized by methods known in the art.
[0020] Experiment 1 Preparation of type III crystals Compound (3) solid (150 mg) was dissolved in 1,4-dioxane / DCM, n-heptane was added dropwise to the solution, stirred for 4 hours, and filtered to obtain crystals. The obtained crystals were vacuum dried at room temperature for 0.5 hours. According to the XRPD measurement result, type III crystals were obtained.
[0021] Experiment 2 Preparation of type III crystals The solid compound (3) was suspended and stirred in ethanol at room temperature for 48 hours, filtered, and vacuum dried at room temperature to obtain crystals. The obtained crystals were heated to 141°C under nitrogen protection. According to the XRPD measurement results, type III crystals of compound (3) were obtained.
[0022] Experiment 3 Scaled production of type III crystals. Compound 3 (1575.3 mg) was weighed into a 100 mL reaction vessel, and THF (35 mL) was added to the reaction vessel with mechanical stirring (rotation speed: approximately 320 rpm), and the compound was dissolved at 50° C. to obtain a clear solution.
[0023] n-Heptane (48 mL) was added dropwise to the reaction vessel, and an appropriate amount of III-type crystals was added in portions as seed crystals during the dropwise addition to obtain a white suspension. The resulting suspension was stabilized at 50°C for 70 min, and then gradually cooled to 25°C at a rate of 0.5°C / min, and then stirred for about 3 days.
[0024] The resulting suspension was filtered under reduced pressure, washed with n-heptane (3 mL), filtered under reduced pressure, and then dried in vacuum at 50° C. for about 5 hours to obtain 1.2 g of a white solid. The results of XRPD showed that the crystalline form (III) was produced.
[0025] The diffraction peak data for the type III crystal of compound (3) is shown in Table 1 above. The XRPD diagram of the III crystal is shown in FIG. The TGA / DSC diagram of the III crystal is shown in FIG. A comparative variable temperature XRPD plot of crystal form III is shown in FIG.
[0026] According to TGA / DSC, the III crystal lost 1.2% weight when heated to 200°C, which may be attributed to a small amount of residual solvent or water on the sample surface. One melting endothermic signal was observed at 237.9°C (onset temperature). From the HPLC result, the sample purity was 99.4 area%. Yield: 68.3%. It was stable in TGA (110°C), and the variable temperature XRPD result showed that the crystal form did not change after heating the III crystal to 150°C under nitrogen protection, as shown in Figure 3. The analysis confirmed that the III crystal was an anhydrous stable crystal form.
[0027] Experiment 4 Type I crystal The compound (3) solid was dissolved in 2-MeTHF, n-heptane was added dropwise at room temperature, and the mixture was stirred for 4 hours to precipitate crystals, which were then filtered and dried in vacuum to obtain compound (3) type I crystals. The XRPD diagram is shown in FIG. 4.
[0028] Using Cu-Kα radiation, the compound (3) type I crystal had characteristic peaks at diffraction angles of 2θ values = 7.94°, 8.79°, 9.68°, 11.56°, 13.74°, 14.37°, 15.98°, 17.78°, 19.39°, and 23.85° in the powder X-ray diffraction pattern.
[0029] [Table 2]
[0030] The TGA / DSC diagram of the I-type crystal of compound (3) is shown in FIG. 5. The crystal lost 13.2% when heated to 110°C, and lost 3.5% when heated to 200°C. Three endothermic signals were observed in the range of 80-140°C. Under nitrogen protection, the I-type crystal was heated to 55°C and then cooled to room temperature, and the sample was taken out and exposed to air for XRPD measurement, and the results are shown in FIG. 6. In the figure, the upper curve is the original diagram of the I-type crystal, the middle curve is the XRPD diagram before heating, and the lower curve is the XRPD diagram after heating to 55°C. According to the figure, the intensity of the diffraction peak of the sample decreased, and according to the NMR result, after heating, the molar ratio of 2-MeTHF to API was 0.25:1.00 (6.5wt%), and 2-MeTHF was reduced by about 3.5wt% compared to before heating. Under the same nitrogen protection conditions, the I-type crystal was heated to 100°C, and the XRPD result is shown in Figure 7. According to the figure, the crystal had already converted to amorphous. According to the NMR result, after heating, the molar ratio of 2-MeTHF to API was 0.09:1.00 (2.4 wt%), which was about 7.6 wt% less than before heating.
[0031] Experiment 5 Type II crystal Compound (3) solid was dissolved in 1,4-dioxane / DCM (1-5 / 10), n-heptane was added dropwise to the solution, and the solution was stirred for 4 hours to precipitate crystals. The crystals were filtered to obtain compound (3) type II crystals, and the XRPD diagram is shown in FIG. 8.
[0032] Using Cu-Kα radiation, the type II crystal has characteristic peaks at diffraction angles of 2θ values of 6.39°, 7.84°, 10.58°, 12.57°, 14.88°, 15.71°, 16.12°, 19.6°, 22.57°, 23.91°, and 30.62° in a powder X-ray diffraction pattern.
[0033] [Table 3]
[0034] After drying in vacuum at room temperature for half an hour, the type II crystal changed its crystal form and transformed into type III crystal. Since type II crystal was unstable and the crystal had already transformed after a short drying period, no further research was carried out on type II crystal.
[0035] Test 6 Type IV crystal The compound (3) solid was suspended and stirred in EtOH at room temperature for 48 hours, and filtered to obtain type IV crystals, whose XRPD diagram is shown in FIG.
[0036] Using Cu-Kα radiation, the IV type crystal had characteristic peaks at diffraction angles of 2θ values = 4.28°, 6.03°, 8.50°, 9.53°, 12.76°, 13.58°, 14.84°, 15.45°, 17.02°, 17.61°, 18.17°, 19.12°, 19.60°, 20.97°, 21.38°, 22.66°, 24.99°, 25.99°, 28.47°, 28.82°, 29.80°, 31.24°, 32.66°, and 36.78° in the powder X-ray diffraction pattern.
[0037] [Table 4]
[0038] After the IV type crystals were vacuum dried at room temperature for 15 minutes, a decrease in the relative intensity of the diffraction peaks was observed. After the dried crystals were left sealed at room temperature for about 5 days, an improvement in the relative intensity of the diffraction peaks and an increase in the number of diffraction peaks were observed. Analysis suggests that the IV type crystals may have absorbed moisture from the air after coming into contact with the air, due to the removal of solvent or water during vacuum drying, and thus improving their crystallinity.
[0039] According to TGA, the IV crystal is unstable at 120° C., loses 10.6%, and is a monohydrate crystal form. Under nitrogen protection, the IV crystal is heated to 141° C., and then XRPD measurement is performed. The result shows that the IV crystal is transformed into the stable III crystal at 141° C.
[0040] Test 7 V type crystal The compound (3) solid was suspended and stirred in EtOAc at room temperature for 48 hours, filtered, and dried in vacuum at room temperature for 15 minutes to obtain type V crystals, the XRPD of which is shown in FIG.
[0041] Using Cu-Kα radiation, the V-type crystal had characteristic peaks at diffraction angles of 2θ values = 4.73°, 9.12°, 11.27°, 13.22°, 15.58°, 17.69°, 18.95°, 21.13°, 22.10°, 24.29°, 26.72°, 27.09°, 28.34°, 29.25°, and 31.76° in the powder X-ray diffraction pattern.
[0042] [Table 5]
[0043] According to the TGA / DSC measurement results, the V-type crystals lost 15.4% weight when heated to 140°C, and then lost 2.8% weight when heated to 240°C, and showed multiple heat traces in the range of 77-203°C. According to the NMR result, the molar ratio of EtOAc to API was 0.40:1.00 (10.2 wt%).
[0044] Variable temperature XRPD measurement was performed on the V-type crystal. After the sample was purged with nitrogen gas for about 20 minutes, a clear decrease in crystallinity was observed. After heating to 90 and 130°C under nitrogen protection, it was converted to almost amorphous, and after heating to 154°C, it was converted to another crystal. Based on the combined analysis of the NMR and TGA results, the V-type crystal is considered to be a solvate.
[0045] Test 8 VI type crystal The compound (3) solid was suspended and stirred in MIBK (methyl isobutyl ketone) at room temperature for 48 hours, filtered, and vacuum dried at room temperature for 15 minutes to obtain type VI crystals, the XRPD of which is shown in FIG.
[0046] Using Cu-Kα radiation, the VI type crystal had characteristic peaks at diffraction angles of 2θ values = 5.01°, 5.62°, 7.62°, 8.98°, 9.67°, 9.99°, 11.11°, 12.12°, 14.22°, 15.02°, 15.79°, 18.01°, 19.37°, 22.55°, 24.18°, 25.15°, 26.22°, 29.21°, 30.29°, 31.74°, and 34.00° in the powder X-ray diffraction pattern.
[0047] [Table 6]
[0048] According to the results of TGA / DSC, the VI type crystal lost 4.9% weight when heated to 70°C, and then lost 5.9% weight when heated to 130°C, and multiple heat traces were observed in the range of 98-210°C.
[0049] Under nitrogen protection, Form VI crystal was heated to 160° C., and the crystal form changed according to the XRPD results.
[0050] Test 9 Type VII crystal The compound (3) solid was suspended and stirred in a mixed solvent of IPA / toluene (v / v, 1:1) at room temperature for 48 hours, filtered, and dried in vacuum at room temperature for 15 minutes to obtain type VII crystals. The XRPD result is shown in FIG. 12.
[0051] Using Cu-Kα radiation, the powder X-ray diffraction pattern of the VII type crystal had characteristic peaks at diffraction angles of 2θ values = 6.80°, 8.59°, 12.36°, 12.77°, 13.68°, 17.24°, 18.30, 19.32°, 20.77°, 22.20°, 24.47°, 27.81°, 29.32°, and 31.67°.
[0052] [Table 7]
[0053] According to the TGA / DSC measurement results, the VII type crystal lost 11.2% when heated to 130° C., and multiple heat traces were observed in the range of 88 to 215° C. Under nitrogen protection, the VII type crystal was heated to 130° C. and then cooled to room temperature, and the sample was taken out and exposed to air for XRPD measurement, and the result showed that the crystal type had changed.
[0054] Test 10 Type VIII crystal The mixture (3) solid was suspended and stirred in a THF / n-heptane (v / v, 1:1) mixed solvent at 50° C. for 48 hours, filtered, and vacuum-dried at room temperature for 15 minutes to obtain type VIII crystals, the XRPD diagram of which is shown in FIG. 13.
[0055] Using Cu-Kα radiation, the type VIII crystal had characteristic peaks at diffraction angles of 2θ values = 5.24°, 7.98°, 8.20°, 10.51°, 10.77°, 12.55°, 13.40°, 14.27°, 15.28°, 16.29°, 16.69°, 17.25°, 18.94°, 19.72°, 21.19°, 23.23°, 24.63°, 26.09°, 26.60°, 30.05°, and 31.77° in the powder X-ray diffraction pattern.
[0056] [Table 8]
[0057] According to the results of TGA / DSC, the VIII type crystal lost 10.6% weight when heated to 160°C, and multiple heat traces were observed in the range of 120-220°C. Under nitrogen protection, the VIII type crystal was heated to 160°C and then cooled to room temperature, and the sample was taken out and exposed to air for XRPD measurement, and the results showed that the crystal type had already changed.
[0058] Test 11 Type IX crystal Compound (3) was dissolved in a THF / CHCl3 mixed solvent at room temperature and evaporated at room temperature to obtain type IX crystals, whose XRPD diagram is shown in FIG.
[0059] Using Cu-Kα radiation, the IX type crystal had characteristic peaks at diffraction angles of 2θ values of 6.47°, 9.57°, 13.56°, 16.84°, 17.61°, 19.36°, 20.06°, 22.45°, and 28.32° in the powder X-ray diffraction pattern.
[0060] [Table 9]
[0061] According to the results of TGA / DSC, the IX type crystal lost 20.3% when heated to 160°C, and multiple heat traces were observed in the range of 130-215°C. After the IX type crystal was left sealed at room temperature for about 3 days, a decrease in crystallinity was observed. Under nitrogen protection, the sample was heated to 95°C and then cooled to room temperature, and the sample was taken out and exposed to air, and an XRPD measurement was performed. The results showed that the crystallinity continued to decrease. Under similar nitrogen protection conditions, the sample was heated to 160°C and then cooled to room temperature, and the sample was taken out and exposed to air, and an XRPD measurement was performed. The results showed that the crystal form changed. By analyzing the results of NMR and TGA together, it is believed that the change in crystal form after heating is due to desolvation, and the IX type crystal is a solvate.
[0062] Test 12 X type crystal The compound (3) solid was suspended and stirred in IPAc (isopropyl acetate) at 50° C. for 48 hours and filtered to obtain type X crystals. The XRPD diagram is shown in FIG.
[0063] Using Cu-Kα radiation, the X-type crystal had characteristic peaks at diffraction angles of 2θ values of 7.72°, 8.91°, 14.10°, 14.79°, 16.95°, 18.39°, 19.53°, 22.06°, 22.53°, 29.81°, and 31.51° in a powder X-ray diffraction pattern.
[0064] [Table 10]
[0065] According to the TGA / DSC results, the X-type crystal lost 7.9% weight when heated to 130°C, and lost 4.5% weight when subsequently heated to 160°C, and multiple heat traces were observed within the range of 126-210°C.
[0066] Variable temperature XRPD measurements were performed on the X-type crystals. The results showed that after heating to 120°C under nitrogen gas purge, the X-type crystals had a shift in the diffraction peak position, and after heating to 130°C, the intensity of the diffraction peaks decreased obviously, and after heating to 145°C, the crystal type changed.
[0067] Test 13 Type XI crystal The compound (3) solid was suspended and stirred in methyl t-butyl ether for 48 hours and filtered to obtain XI type crystals, the XRPD diagram of which is shown in FIG.
[0068] Using Cu-Kα radiation, the XI type crystal had characteristic peaks at diffraction angles of 2θ values = 8.42°, 11.29°, 13.02°, 14.72°, 15.01°, 16.55°, 17.23°, 18.49°, 18.90°, 19.67°, 21.37°, 22.42°, 22.67°, 24.14°, 25.08°, 25.44°, 26.02°, 26.44°, 27.63°, 28.14°, 29.67°, 30.32°, 32.95°, 35.96°, 36.59°, and 39.03° in the powder X-ray diffraction pattern.
[0069] [Table 11]
[0070] According to the TGA / DSC test results, the XI type crystal lost 19.3% in weight when heated to 120°C, and multiple heat traces were observed at temperatures between 95 and 210°C.
[0071] Test 14 Type XII crystal Compound (3) type III crystals or type XI crystals were suspended and stirred in pure water at room temperature for about 24 hours, filtered, and dried overnight at room temperature to obtain type XII crystals, the XRPD diagram of which is shown in FIG.
[0072] Using Cu-Kα radiation, the XII-type crystal had characteristic peaks at diffraction angles of 2θ values of 8.52°, 11.25°, 14.78°, 15.45°, 17.10°, 19.58°, 22.74°, 23.94°, 26.36°, 30.28°, 31.17°, and 33.11° in a powder X-ray diffraction pattern.
[0073] [Table 12]
[0074] The XII form was converted to amorphous after drying in vacuum at room temperature for 10 minutes. TGA / DSC characterization was performed on the sample that was air-dried at room temperature, and the results showed that the sample lost 59.6% weight when heated to 120°C and showed multiple heat traces in the range of 50-240°C.
[0075] Test 15 XIII type crystal The III type crystals or the XII type crystals were suspended and stirred in methanol at room temperature for about 24 hours, and filtered to obtain the XIII type crystals, the XRPD diagram of which is shown in FIG.
[0076] Using Cu-Kα radiation, the XIII type crystal had characteristic peaks at diffraction angles of 2θ values of 6.15°, 7.81°, 9.46°, 13.92°, 14.39°, 14.72°, 15.56°, 17.13°, 17.71°, 18.99°, 23.59°, 25.01°, 25.79°, 26.70°, 28.65°, and 30.56° in a powder X-ray diffraction pattern.
[0077] [Table 13]
[0078] The XIII type crystals were unstable, and the crystal form changed after about 2 hours of open drying at room temperature. In addition, when the XIII type crystals were film-coated and subjected to XRPD measurement, new XIV type crystals were observed, and it was speculated that the XIV type crystals were in an unstable intermediate state and would convert to the XIII type crystals when removed from the solvent. The XRPD comparison diagram is shown in Figure 19. Rapid crystal form conversion was observed for the XIII type crystals at room temperature.
[0079] Test 16 Type XIV crystal The XIII type crystal was left in a solvent environment at room temperature and converted to the XIV type crystal, the XRPD diagram of which is shown in Figure 20. After leaving the solvent environment, it was converted to the XIII type crystal.
[0080] Using Cu-Kα radiation, the XIV type crystal had characteristic peaks at diffraction angles of 2θ values of 6.94°, 8.75°, 9.21°, 11.16°, 12.82°, 13.82°, 15.56°, 17.59°, 19.67°, 20.93°, 22.51°, 24.35°, 29.58°, and 31.37° in the powder X-ray diffraction pattern.
[0081] [Table 14]
[0082] Test 17 XV type crystal The XII type crystal was allowed to stand in an environment of 40 to 90° C. for 3 to 12 days to obtain the XV type crystal, the XRPD diagram of which is shown in FIG.
[0083] Using Cu-Kα radiation, the XV type crystal had characteristic peaks at diffraction angles of 2θ values = 9.247°, 9.982°, 13.4°, 15.781°, 16.55°, 16.929°, 18.704°, 20.14°, 20.78°, 21.1°, 22.497°, 23.654°, 25.013°, 25.667°, 27.026°, 28.186°, 22.715°, 28.822°, 29.265°, and 29.762° in the powder X-ray diffraction pattern.
[0084] [Table 15]
[0085] Crystal type XV lost 2.2% weight when heated to 120° C., and a crystal type transformation occurred.
[0086] Test 18 XVI type crystal and XVII type crystal Compound (3) was suspended and stirred in a mixed solvent of ethanol / water (volume ratio 8:2) for 24 hours, and filtered to obtain type XVI crystals. The XRPD pattern is shown in FIG. 22, and the DSC-TGA diagram is shown in FIG.
[0087] The single crystal data for the XVI crystal is shown in Table 16.
[0088] [Table 16]
[0089] A three-dimensional view of the single crystal X-ray diffraction molecule of the XVI type crystal is shown in FIG. 24, which shows that each XVI type crystal contains four molecules of water of crystallization.
[0090] After drying in vacuum at room temperature for 24 hours, the XVI type crystals showed obvious dehydration (14.39% weight loss) and changed into the monohydrate type XVII crystals after losing three molecules of water. The XRPD pattern is shown in FIG. 25, and the DCS-TGA diagram is shown in FIG. 26.
[0091] Crystal type XVI was heated to 55° C. in a nitrogen atmosphere and kept at that temperature for 2 to 24 hours, and according to the XRPD pattern, crystal type XVII was similarly obtained.
[0092] Crystal XVII was dried at 90° C. for 1 to 24 hours, losing one molecule of water (5.47% weight loss) to give crystal XVIII, which is an anhydrous form.
Claims
1. A type III crystal of compound (3), wherein the type III crystal has characteristic peaks at diffraction angles of 2θ values of 8.83°, 16.08°, 16.53°, 17.67°, 18.19°, 25.52°, 26.20°, and 27.05° in a powder X-ray diffraction pattern using Cu-Kα radiation, with the proviso that changes in the 2θ values are allowed within an error range. 【Chemistry 1】
2. The III-type crystal of compound (3) according to claim 1, having the diffraction peaks shown in the table below. 【Table 1】
3. A method for producing the III-type crystal of compound (3) according to claim 1 or 2, comprising the steps of: The method includes dissolving compound (3) in 1,4-dioxane / DCM in a volume ratio of 1 to 5:10, adding petroleum ether or a lower alkane to the solution, leaving or stirring for 1 to 24 hours, preferably 3 to 10 hours, more preferably 4 hours, to precipitate crystals, filtering the crystals, and subjecting the resulting crystals to a vacuum treatment at 25 to 120° C., preferably 40 to 60° C., for 1 to 24 hours, preferably 3 to 5 hours, to obtain type III crystals.
4. A method for producing the III-type crystal of compound (3) according to claim 1 or 2, comprising the steps of: The method includes stirring compound (3) in ethanol at room temperature for 2 to 72 hours, preferably 20 to 60 hours, more preferably 48 hours, filtering, and drying in vacuum at room temperature to obtain crystals, and heating the obtained crystals to 120 to 150°C, preferably 140 to 145°C, more preferably 141°C under nitrogen protection to obtain type III crystals of compound (3).
5. A method for producing the III-type crystal of compound (3) according to claim 1 or 2, comprising the steps of: The method includes dissolving compound (3) in THF or methyl THF, adding petroleum ether or a lower alkane to the resulting solution, adding an appropriate amount of type III crystal as a seed crystal, obtaining a white suspension, stirring or leaving the resulting suspension at 40°C to 70°C, preferably 50°C, for 1 to 4 hours, preferably 60 to 70 minutes, gradually lowering the temperature to room temperature, stirring or leaving for an appropriate period of time, and filtering the resulting suspension under reduced pressure at room temperature, washing with n-heptane, and drying in vacuum at 40°C to 80°C, preferably 50°C, to obtain type III crystals; The lower alkane may be, for example, but is not limited to, pentane, hexane, octane, nonane, or decane.
6. A pharmaceutical composition comprising the crystalline form III of compound (3) according to claim 1 or 2, and any pharmaceutical auxiliary.
7. Use of the crystalline form III of compound (3) according to claim 1 or 2, or the pharmaceutical composition according to claim 6, for the manufacture of a drug or pharmaceutical preparation for anti-HIV or AIDS treatment.
Citation Information
Patent Citations
Crystal form, preparation method, and application of 4'-substituted nucleoside
WO2020007070A1
